Neonatal bone marrow transplantation for severe combined immunodeficiency. Issue 2 (1st September 2001) - Kane, L; Gennery, A R; Crooks, B N A; Flood, T J; Abinun, M; Cant, A J
Abstract : AIMS: To evaluate outcome following neonatal bone marrow transplantation (BMT) for severe combined immunodeficiency (SCID) when there is a family history of a previously affected sibling, and to compare results with those published for in utero BMT. METHODS: A retrospective review of cases referred and transplanted between 1987 and 1999, focusing on infectious and graft versus host disease (GvHD) complications after BMT, and T and B lymphocyte function. Thirteen patients received 18 stem cell transplants: four whole marrow, one cord blood, 10 parental T cell depleted (TCD) haplo-identical, and three TCD unrelated donor BMT. Nine were conditioned with busulphan and cyclophosphamide. RESULTS: All are alive and well (six months to 11.5 years after BMT). Six had grade I–II acute GvHD and two chronic GvHD (now resolved). Three had a top up BMT for poor T cell function, one had a third BMT for graft failure and chronic GvHD, and one had a third BMT for graft failure. Twelve have good in vitro proliferation to T cell mitogens, and all have normal serum IgA levels. Three receive intravenous immunoglobulin; for one of these, it is less than one year since BMT. Nine are above the 2nd centile, and 10 of 12 old enough to be assessed have normal neurodevelopment. CONCLUSION: These results are better than those published for in utero BMT for SCID. Early postnatal BMT should be the preferred option in neonatal SCID.